The assessment of collateral communication after hybrid repair for Crawford extent II thoraco-abdominal aortic aneurysms†. (16th February 2015) - Shijo, Takayuki; Kuratani, Toru; Shirakawa, Yukitoshi; Torikai, Kei; Shimamura, Kazuo; Sakamoto, Tomohiko; Watanabe, Yoshiki; Maeda, Noboru; Tomiyama, Noriyuki; Sawa, Yoshiki
Abstract : OBJECTIVES: The repair of extensive thoraco-abdominal aortic aneurysms (TAAAs) is invasive and carries a high risk for spinal cord injury (SCI). The aim of this study was to assess the early results and collateral circulation to the spinal cord after hybrid repair for Crawford extent II aortic aneurysms. METHODS: Between 1997 and 2013, we performed 128 thoracic endovascular aortic repair (TEVAR) procedures for TAAAs. This study reviews 12 patients who underwent hybrid TEVAR for a Crawford extent II aortic aneurysm (mean age: 56 years, 6 men, chronic dissection: 10). Aortic arch repair was performed to create a proximal landing zone and visceral debranching bypass was performed to create a distal landing zone at separate stages prior to TEVAR. Subsequently, a stent graft was deployed to cover the residual downstream aorta. TEVAR was generally performed the day after the final debranching procedure. Cerebrospinal fluid drainage was performed, and the mean blood pressure was maintained at >90 mmHg in all cases. RESULTS: The median operation time for TEVAR was 94 min (range: 71–421 min) and the mean blood loss was 300 ml (range: 130–1350 ml). No SCI or in-hospital death was observed after TEVAR. Multidetector computed tomography identified three arteries (subclavian artery, external iliac artery and internal iliac artery) providing collateral circulation to spinal segmental arteries (SAs). In all cases, mid-thoracic SAs (Th5−8) and low lumbar SAs (L2−5) were fed by the subclavian artery and the internal iliac artery, respectively. Additionally, low thoracic to high lumbar SAs (Th9-L1) communicated with the subclavian artery via the lateral thoracic wall and/or the external iliac artery via the abdominal wall. CONCLUSIONS: We achieved satisfactory early and mid-term outcomes with hybrid repair for Crawford extent II TAAAs. Furthermore, collateral circulation to SAs was maintained during and after TEVAR regardless of the extent of the aortic repair.